Gender dan Perceraian: Kasus Cerai Gugat Di Pengadilan Agama Bekasi - Mazro’atus Sa’adah (MUWAZAH : jurnal kajian gender, 2018)
This study explores the causes of divorce in Pengadilan Agama Bekasi, as well as the relation with gender issues. This study uses a qualitative approach. Data collection techniques with interviews, observation and literature studies. Analysis techniques using interactive models. The results show that the factors causing the divorce are economic factors, irresponsible husbands' factors, domestic factors of abuse, factors of infidelity and polygamy. The higher the gender awareness of a woman, the higher of the divorce case. This gender awareness is usually owned by women who have higher education, women who are aware of their rights and obligations, independent women, and who are aware of husband and wife relations.